2022
DOI: 10.1101/2022.12.05.519224
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of a population of descending neurons in the optomotor response in flyingDrosophila

Abstract: To maintain stable flight, animals continuously perform trimming adjustments to compensate for internal and external perturbations. Whereas animals use many different sensory modalities to detect such perturbations, insects rely extensively on optic flow to modify their motor output and remain on course. We studied this behavior in the fruit fly, Drosophila melanogaster, by exploiting the optomotor response, a robust reflex in which an animal steers so as to minimize the magnitude of rotatory optic flow it per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…In addition, several DNs (DNp31, DNg02 and DNp03 examples in Figure 12G) as well as Tect INs themselves take pathways to indirect control MNs–namely to the tergopleural and pleurosternal MNs which may control thoracic stiffness or tension. While the roles of the ICMs in flight have not received as much investigation as other muscle categories, it appears that concurrent control of PMs and ICMs are important for the function of DNs such as the DNg02s which modulate wingbeat amplitude in flight (Namiki et al, 2022; Palmer et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several DNs (DNp31, DNg02 and DNp03 examples in Figure 12G) as well as Tect INs themselves take pathways to indirect control MNs–namely to the tergopleural and pleurosternal MNs which may control thoracic stiffness or tension. While the roles of the ICMs in flight have not received as much investigation as other muscle categories, it appears that concurrent control of PMs and ICMs are important for the function of DNs such as the DNg02s which modulate wingbeat amplitude in flight (Namiki et al, 2022; Palmer et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…While the actual function of this motif is unknown, one intriguing possibility is that the recurrent excitatory and inhibitory connections in the Tect INs and IN06B066 group 16779 form an inhibition-stabilized network, where a stable level of excitatory activity can be maintained in the excitatory subnetwork with feedback inhibition from the inhibitory subnetwork serving to prevent runaway excitation (Sadeh and Clopath, 2021). Such networks are notable for the paradoxical observation that excitation to the inhibitory neurons decreases the steady-state activity for both the inhibitory and excitatory neuron populations (Sadeh and Clopath, 2021) (Namiki et al, 2022;Palmer et al, 2022).…”
Section: Wing Power Output Is Likely Driven By Diffuse Excitatory Con...mentioning
confidence: 99%
“…wing beat amplitude (a major contributing factor to yaw torque) (114), re-vealed aPKC/FoxP co-expressing MNs innervating a specific subset of these muscles (Figure 3), corroborating our hypothesis. MNs in the VNC (117,118). This suggests that in the ventral nerve cord, the steering motor neurons are the only neurons that OMRs and operant self-learning share.…”
Section: Discussionmentioning
confidence: 94%
“…From this realization, the question arises if there are other shared neural components between OMRs and operant learning in addition to the doubly labeled steering MNs. Evidence suggests that the steering commands for OMRs are communicated directly from visual areas in the brain via (both identified and yet to be identified) descending neurons with direct synaptic connections onto the steering MNs in the VNC (117,118). This suggests that in the ventral nerve cord, the steering motor neurons are the only neurons that OMRs and operant self-learning share.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the observation that a population of 15 DNs can modulate wing beat amplitude 29 and that the activation of individual DNs has a lower probability of driving take-off than co-activation of multiple DNs 30 . Beyond controlling kinematics, it has also been shown that DNs can convey sensory information 28,31 and that they may be modulatory 32,33,34,35 . All of these observations suggest that, rather than being low-dimensional, DN control of behavior is population-based or high-dimensional: the brain flexibly engages larger populations of DNs to construct and mediate complete behaviors.At first glance, these two models-command-like versus population-based DN behavioral controlappear to be incompatible.…”
mentioning
confidence: 99%